Classification performance of clinical risk scoring in suspected acute coronary syndrome beyond a rule-out troponin profile. Issue 9 (1st July 2021) - Khan, Ehsan; Lambrakis, Kristina; Blyth, Andrew; Seshadri, Anil; Edmonds, Michael J R; Briffa, Tom; Cullen, Louise A; Quinn, Stephen; Horsfall, Matthew; Morton, Erin; French, John K; Papendick, Cynthia; et al.
Graphical Abstract: Abstract: Aims: High-sensitivity cardiac troponin strategies can provide risk stratification in patients with suspected acute coronary syndrome (ACS) in the emergency department (ED). This study evaluated whether clinical risk scoring improves the classification performance of a rule-out profile in suspected ACS. Methods and results: Patients presenting to ED with suspected ACS as part of the RAPID-TnT trial randomized to the intervention arm were included. Results ≥ 5 ng/L were available for all participants in this analysis. We evaluated the Thrombolysis In Myocardial Infarction (TIMI) risk score, History ECG Age Risk factors Troponin (HEART) score, and Emergency Department Assessment of Chest pain Score (EDACS) in addition to a rule-out profile based on the 0/1-h high-sensitivity cardiac troponin T protocol (<5 ng/L or ≤ 12 ng/L and a change of <3 ng/L at 1-h) using test performance parameters focusing on low-risk groups to identify the primary endpoint (TIMI ≤  1, HEART ≤  3, EDACS < 16). Primary endpoint was a composite of type 1/2 myocardial infarction (MI) at index presentation and all-cause mortality or type 1/2 MI at 30 days. A total of 3378 participants were enrolled between August 2015 and April 2019 of which 108 were ineligible/withdrew consent (intervention arm: n  = 1638). Sensitivity, specificity, negative predictive value (NPV), and area under the curve (AUC) of the rule-out profile was 94.4%, 76.8%, 99.6%, and 0.86, respectively with 72.9% identified as 'low-risk'. Adding the clinical risk scores did not improve the sensitivity, NPV, or AUC with significantly lower specificity and 'low-risk' classified participants. Conclusions: Addition of clinical risk scores to rule-out profile did not demonstrate improved classification performance for identifying the composite of type 1/2 MI at index presentation and all-cause mortality or type 1/2 MI at 30 days. Clinical trials registration: URL: https://www.anzctr.org.au . Reg. No. ACTRN12615001379505.